Six-minute walk test in children and adolescents with renal diseases: tolerance, reproducibility and comparison with healthy subjects (Clinics, 2016)
OBJECTIVES: To evaluate exercise tolerance and the reproducibility of the six-minute walk test in Brazilian children and adolescents with chronic kidney disease and to compare their functional exercise capacities with reference values for healthy children. METHODS: This cross-sectional study assessed the use of the six-minute walk test in children and adolescents aged 6-16 with stage V chronic kidney disease. For statistical analysis of exercise tolerance, including examinations of correlations and comparisons with reference values, the longest walked distances were considered. The reproducibility of the six-minute walk test was assessed using intraclass correlation coefficients. RESULTS: A total of 38 patients (14 females and 24 males) were evaluated, including 5 on peritoneal dialysis, 12 on hemodialysis and 21 who had undergone renal transplantation, with a median age of 11.2 years (6.5-16). The median walked distance was 538.5 meters (413-685) and the six-minute walk test was found to be reproducible. The walked distance was significantly correlated with age (r=0.66), weight (r=0.76), height (r=0.82), the height Z score (r=0.41), hemoglobin (r=0.46), hematocrit (r=0.47) and post-test systolic blood pressure (r=0.39). The chronic kidney disease patients predicted walked distance was 84.1% of the reference value according to age, 90.6% according to age-corrected height and 87.4% according to a predictive equation. CONCLUSIONS: The stage V chronic kidney disease patients had a significantly decreased functional exercise capacity, as measured by the six-minute walk test, compared with the healthy pediatric reference values. In addition, the six-minute walk test was shown to be well tolerated, reliable and applicable as a low-cost tool to monitor functional exercise capacity in patients with renal disease.